2012
DOI: 10.2337/db12-0558
|View full text |Cite
|
Sign up to set email alerts
|

31P-Magnetization Transfer Magnetic Resonance Spectroscopy Measurements of In Vivo Metabolism

Abstract: Magnetic resonance spectroscopy offers a broad range of noninvasive analytical methods for investigating metabolism in vivo. Of these, the magnetization-transfer (MT) techniques permit the estimation of the unidirectional fluxes associated with metabolic exchange reactions. Phosphorus (31P) MT measurements can be used to examine the bioenergetic reactions of the creatine-kinase system and the ATP synthesis/hydrolysis cycle. Observations from our group and others suggest that the inorganic phosphate (Pi) → ATP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
89
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(93 citation statements)
references
References 103 publications
4
89
0
Order By: Relevance
“…Interestingly, a cross-sectional study of 15 normal subjects [36], significant correlations were found between the resting Pi-ATP exchange rate and a restingischaemia 31 P MRS measure of resting ATP synthesis rate (despite the order-of-magnitude difference in absolute numbers), and PCr-recovery based measures of mitochondrial function (despite the logical distinctness of ATP turnover and oxidative capacity, as mentioned above, and for reasons which are so far unexplained [10]. This first of these correlations, together with some observations of clinical or experimental changes in Pi-ATP exchange in physiologically expected directions [37] (again, notwithstanding the order-of-magnitude error), is sometimes described as supporting [37] or even validating [30] the Pi-ATP exchange measurement. However, as almost nothing is known about what determines the overwhelmingly dominant non-mitochondrial component of the measurement [10], this interpretation remains problematic.…”
Section: Discussionmentioning
confidence: 77%
“…Interestingly, a cross-sectional study of 15 normal subjects [36], significant correlations were found between the resting Pi-ATP exchange rate and a restingischaemia 31 P MRS measure of resting ATP synthesis rate (despite the order-of-magnitude difference in absolute numbers), and PCr-recovery based measures of mitochondrial function (despite the logical distinctness of ATP turnover and oxidative capacity, as mentioned above, and for reasons which are so far unexplained [10]. This first of these correlations, together with some observations of clinical or experimental changes in Pi-ATP exchange in physiologically expected directions [37] (again, notwithstanding the order-of-magnitude error), is sometimes described as supporting [37] or even validating [30] the Pi-ATP exchange measurement. However, as almost nothing is known about what determines the overwhelmingly dominant non-mitochondrial component of the measurement [10], this interpretation remains problematic.…”
Section: Discussionmentioning
confidence: 77%
“…Since then, this technique has been widely applied to measure CK reaction rate in heart, brain, and skeletal muscle (17,73,(112)(113)(114)(115)(116)(117). P i -to-ATP flux has also been investigated in liver, heart, Quant Imaging Med Surg 2017;7(6):707-726 qims.amegroups.com brain, and skeletal muscle (17,(118)(119)(120)(121). Metabolic abnormalities associated with various diseases including diabetes (17,120), heart failure (7), and stroke (122) have also been evaluated using this technique.…”
Section: Quantification Of Atp Synthesis Rates By 31p Magnetization-tmentioning
confidence: 99%
“…Since each acquisition is followed by a long waiting period to reestablish the equilibrium conditions, acquisition time of an MT experiment is typically very long, with waiting time amounts to >90% of the total acquisition time. Further, due to the relatively small signal change in P i (~20%), quantification of ATP synthesis rate via ATP synthase has been quite limited (17).…”
Section: Quantification Of Atp Synthesis Rates By 31p Magnetization-tmentioning
confidence: 99%
See 1 more Smart Citation
“…The applied saturation transfer method for assessing fATP by means of 31 P-MRS has been validated in a variety of in vitro systems and in human muscle biopsy samples, as reviewed recently (37). The limitations of this approach are that this method provides a measure of ATP synthesis/ hydrolysis cycle at rest driven by energy demands rather than maximal oxidative capacity and that differences in individual mitochondrial content are not taken into account.…”
Section: Discussionmentioning
confidence: 99%